Genome‐wide association analyses of plant growth traits during the stem elongation phase in wheat. Issue 12 (19th August 2018) - Guo, Zifeng; Liu, Guozheng; Röder, Marion S.; Reif, Jochen C.; Ganal, Martin W.; Schnurbusch, Thorsten
Summary: One of the primary objectives of wheat breeding was to increase grain yield. Floral abortion during the stem elongation phase (SEP) leads to a loss of more than 50% of the grain number potential. In this study, we quantified 75 plant growth‐associated traits at seven stages during the SEP and mapped 15 696 single nucleotide polymorphism (SNP) markers in 210 accessions of wheat ( Triticum aestivum ). Our genomewide association study identified trait‐associated SNPs that are shared among various stages of the SEP, as well as SNPs that are shared between plant growth traits and grain yield in the field. The genomic selection analysis shows variation among the prediction abilities of various traits and stages. Furthermore, we found that the allelic variants of Ppd‐D1 (chromosome 2D) and Rht‐D1 (chromosome 4D) loci affect some plant growth traits (e.g. leaf area and spike length). These results have identified a narrow time window within the SEP in which plant growth traits can be manipulated to alter grain yield. This suggests that there may be multiple ways to regulate plant growth during the SEP, to ultimately influence grain number in wheat.